2021
DOI: 10.3389/ffunb.2021.637817
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the Stable Fly, Stomoxys calcitrans, L. 1758 (Diptera: Muscidae) by the Entomopathogenic Fungi Metarhizium anisopliae (Hypocreales: Clavicipitaceae) Negatively Affects Its Survival, Feeding Propensity, Fecundity, Fertility, and Fitness Parameters

Abstract: Entomopathogenic fungi can cause substantial mortality in harmful insects. Before killing the insect, these pathogens start by negatively affecting the biological parameters of the host. Prior to our study, the information about how fungal exposure affects the biological parameters of the stable fly, Stomoxys calcitrans was still elusive. Therefore, we aimed to assess the infection of S. calcitrans with some Metarhizium anisopliae strains, and their impact on feeding, fecundity, fertility and other life-histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We showed that S. calcitrans was significantly more susceptible to Beauveria infection than to Isaria or Metarhizium. Interestingly, in other studies, M. anisopliae strains were capable of infecting and causing high mortality of stable flies under in vitro conditions (López-Sánchez et al, 2012;Weeks et al, 2017;Baleba et al, 2021) and were selected for field trials to control the stable fly (Cruz-Vazquez et al, 2015). To the best of our knowledge, there are no data in the literature regarding the susceptibility of S. calcitrans to B. pseudobassiana.…”
Section: Pathogenicity Of Entomopathogenic Fungi To Stable Fly Adults...mentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that S. calcitrans was significantly more susceptible to Beauveria infection than to Isaria or Metarhizium. Interestingly, in other studies, M. anisopliae strains were capable of infecting and causing high mortality of stable flies under in vitro conditions (López-Sánchez et al, 2012;Weeks et al, 2017;Baleba et al, 2021) and were selected for field trials to control the stable fly (Cruz-Vazquez et al, 2015). To the best of our knowledge, there are no data in the literature regarding the susceptibility of S. calcitrans to B. pseudobassiana.…”
Section: Pathogenicity Of Entomopathogenic Fungi To Stable Fly Adults...mentioning
confidence: 99%
“…Although a high susceptibility of adult flies to entomopathogenic fungi was demonstrated, larvae and pupae were either tolerant or only weakly susceptible to infection (e.g. López-Sánchez et al, 2012;Cruz-Vazquez et al, 2015;Baleba et al, 2021). Even, antifungal activity of S. calcitrans larvae against the fungi was documented (Moraes et al, 2014).…”
Section: Pathogenicity Of Entomopathogenic Fungi To Stable Fly Adults...mentioning
confidence: 99%
See 1 more Smart Citation